Reprimo as a modulator of cell migration and invasion in the MDA-MB-231 breast cancer cell line. Issue 1 (December 2016) - Buchegger, Kurt; Ili, Carmen; Riquelme, Ismael; Letelier, Pablo; Corvalán, Alejandro; Brebi, Priscilla; Huang, Tim; Roa, Juan
Abstract Background Reprimo (RPRM), a highly glycosylated protein, is a new downstream effector of p53-induced cell cycle arrest at the G2/M checkpoint, and a putative tumor suppressor gene frequently silenced via methylation of its promoter region in several malignances. The aim of this study was to characterize the epigenetic inactivation and its biological function in BC cell lines. Methods The correlation betweenRPRM methylation and loss of mRNA expression was assessed in six breast cancer cell lines by methylation specific PCR (MSP), 5′-Aza-2′-deoxycytidine treatment and RT-PCR assays. MDA-MB-231 cells were chosen to investigate the phenotypic effect ofRPRM in cell proliferation, cell cycle, cell death, cell migration and invasion. Results In the cancer methylome system (CMS) (web-based system for visualizing and analyzing genome-wide methylation data of human cancers), the CpG island region ofRPRM (1.1 kb) was hypermethylated in breast cancer compared to normal breast tissue; more interesting still was that ERα(+) tumors showed higher methylation intensity than ERα(−). Downregulation ofRPRM mRNA by methylation was confirmed in MDA-MB-231 and BT-20 cell lines. In addition, overexpression ofRPRM in MDA-MB-231 cells resulted in decreased rates of cell migration, wound healing and invasion in vitro. However, RPRM overexpression did not alter cell viability, phosphatidylserine (PS) translocation or G2/M cell cycle transition. Conclusion Taken together, these data suggest thatRPRM is involved in decreased cell migration and invasion in vitro, acting as a potential tumor suppressor gene in the MDA-MB-231 cell line.